Integration of Educational Values in Learning Citizenship - Niemaz Asmarani Ningtyas (International Journal of Students Education, 2024)
The aim of this study about role of deep integration diverse background behind social own potency for grow trust and become social capital carried by responsible individuals answer. However, on the other hand, globalization pampering public with various importance, especially in Indonesia. Research methods used in the article is a Literature review. Research result showing that Citizenship Education is very supportive education character in carry out the learning process in class. Citizenship Education (Pkn) brings life return character appropriate citizens with Pancasila values, such as devotion, faith, honesty, caring and ethics or polite polite. Citizenship Education (PKn) is the right means for implement values education character to participant educate.